2022
DOI: 10.1136/bmjopen-2021-051131
|View full text |Cite
|
Sign up to set email alerts
|

How the reduction of working hours could influence health outcomes: a systematic review of published studies

Abstract: ObjectivesThe health effects of work-time arrangements have been largely studied for long working hours, whereas a lack of knowledge remains regarding the potential health impact of reduced work-time interventions. Therefore, we conducted this review in order to assess the relationships between work-time reduction and health outcomes.DesignSystematic review of published studies. Medline, PsycINFO, Embase and Web of Science databases were searched from January 2000 up to November 2019.OutcomesThe primary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…Another related discussion concerns the reduction of weekly working days with full wage compensation (i.e., a 4-day week). Having one day free in a week could be considered as having a brief vacation every week and some studies indeed found positive effects on well-being indicators (see reviews of Campbell, 2023; Jansen-Preilowski et al, 2020; Voglino et al, 2022). In 4-day-week schedules, work-related strain accumulation could possibly be reduced by more frequent rest periods (e.g., having a day off in the middle of the week) or more frequent forms of “short vacations” in terms of extended weekends.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another related discussion concerns the reduction of weekly working days with full wage compensation (i.e., a 4-day week). Having one day free in a week could be considered as having a brief vacation every week and some studies indeed found positive effects on well-being indicators (see reviews of Campbell, 2023; Jansen-Preilowski et al, 2020; Voglino et al, 2022). In 4-day-week schedules, work-related strain accumulation could possibly be reduced by more frequent rest periods (e.g., having a day off in the middle of the week) or more frequent forms of “short vacations” in terms of extended weekends.…”
Section: Discussionmentioning
confidence: 99%
“…This mainly concerns compressed workweek models (i.e., reduction of weekly working days with concurrent extension of daily working hours). However, also for models with a proportional reduction in weekly working hours (Voglino et al, 2022) it was sometimes found that daily fatigue increases (Campbell, 2023), which would require having several days off uninterrupted after the workdays (Blasche et al, 2017). Thus, it seems warranted that this stream of research should be integrated with vacation research in future studies.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Additionally, bearing in mind the fact that women, in general, work fewer hours per week than men, and have less productivity loss at work, the practical implication could be considering shortening the expected working week. A systematic review conducted by Voglino et al, in 2022, already proved the positive impact of reduced working hours on the quality of life at work, sleep, and stress [44]. However, work flexibility, which combines work from home and at the office, might have a different impact on women and men [45], and international, culture-specific research might inform national decision-makers about the optimal working schemes.…”
Section: Diskusijamentioning
confidence: 99%
“…Takođe, imajući u vidu činjenicu da žene, opšte uzev, rade manji broj sati nedeljno od muškaraca, a da imaju manji gubitak produktivnosti na poslu, praktična implikacija bi mogla biti razmatranje skraćivanja očekivane radne nedelje. Sistematski pregled koji su sproveli Voglino i saradnici, 2022. godine, već je dokazao pozitivno dejstvo smanjenja broja radnih sati na kvalitet života na radnom mestu, kao i na spavanje i nivo stresa [44]. Međutim, fleksibilnost na poslu, koja omogućava kombinovanje rada od kuće i na radnom mestu, mogla bi da ima različito dejstvo na žene i muškarce [45], a međunarodno istraživanje, specifično za različite kulture, moglo bi da donese saznanja koja bi pomogla donosiocima odluka na nacionalnom nivou pri određivanju optimalnih obrazaca rada.…”
Section: Diskusijaunclassified
“…Part time work may also reduce the physical and psychic strain for many employees. Previous research has indicated quite clearly that probabilities for developing both physical and mental problems increase with the number of hours worked (Bannai & Tamakoshi, 2014;Sparks et al, 1997), and that a reduction in working hours seems to reduce both physical and mental problems for employees (Voglino et al, 2022). Although most of these studies focus on working longer hours than "normal" (usually de ned as the standard number of hours per week de ned in the national legislation and/or agreements between labor unions and employers' unions), they may also be relevant for employees working less than "normal".…”
mentioning
confidence: 98%